(3CSGdjH GdHMK GdYdej aj GdYdhe GdELJeGYjI hGdEfSGfjI (B/s - (3ZQGjHI, ahRjs; (3OgeT, fYje hBNQhfs ((3YeGf(B: s (3OGQ hGFd ddfTQ hGdJhRjY(B, s, 2002)
(3eONd aj GdHMK GdYdej(B- (3eQGMd GdHMK GdYdej(B- (3hSGFd LeY GdHjGfGJ(B- (3WQb YQV GdHjGfGJ(B- (3JMdjd GdHjGfGJ GdEMUGFjI(B.s
Keywords: (3GdHMK GdYdejs; (3GdYdhe GdELJeGYjIs; (3GdYdhe GdEfSGfjIs